Towards Sustainability Goals in the Portuguese Ornamental Stone Industry's Supply Chain 4.0 - Duarte de Almeida, I.; da Silva, Agostinho; C. Rabadão (The 7th Edition of the Global Stone Congress, 2023)
In the age of Industry 4.0 (I4.0), the advent of new digital disruptions has brought about a positive impact on supply chains (SC). This has caught the attention of both researchers and practitioners, who are now exploring the potential of these disruptions, especially in relation to sustainability. However, despite this growing interest, the research on this subject remains in its early stages and lacks cohesion, with limited collaboration between academia and policymakers. Thus, the aim of this paper is to investigate how these technologies can redefine company processes and SC in the Portuguese ornamental stone (POS) industry. The primary goal is to identify novel capabilities within the SCOR model that can contribute to sustainable performance and facilitate the achievement of the 17 Sustainable Development Goals (SDGs).